Pengaruh Literasi Keuangan dan Inklusi Mahasiswa UIN Sunan Gunung Djati Bandung Terhadap Penggunaan Sistem Financial Technology - Nabil Muhammad Alawi; Vemy Suci Asih; Dadang Husen Sobana (Jurnal Maps (Manajemen Perbankan Syariah), 2020)
This study aims to determine how much influence financial literacy and inclusion have on the use of the financial technology system. This research is motivated by the widespread use of financial technology among students. Financial technology helps to buy and selling transactions so that the payment system becomes more economical and efficient and remains active. The method used in this research is quantitative through a descriptive analysis approach. Data collection used questionnaires with research samples from UIN Sunan Gunung Djati Bandung. The results showed the effect of financial literacy, as evidenced by the usefulness indicators and linear ease indicators on the use of the financial technology system for students of UIN Sunan Gunung Djati Bandung. Respondents of 48% admit that literacy regarding the use of financial technology has been felt and is proven by the respondent's knowledge of financial technology, which can facilitate the process of business transactions or services. Also, research on the effect of inclusion is in line with the use of the financial technology system. Respondents of 70% admit that the development of financial technology at this time can be done to make online payments.